2022
DOI: 10.1002/ecs2.4184
|View full text |Cite
|
Sign up to set email alerts
|

Recurring wildfires provoke type conversion in dry western forests

Abstract: Recent wildfires across western North America have burned with uncharacteristically high severity, representing a substantial departure from natural fire regimes. In mixed‐conifer and pine–oak ecosystems of the southern Cascade Range, widespread shifts in stand structure and composition have led to a diversity of post‐wildfire vegetation responses. When recent wildfire “footprints” reburn in subsequent fires, their recovery pathways are complex. In order to understand the effects of overlapping mixed‐severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
2
1
0
Order By: Relevance
“…In this, at low burn severities mesophytic species were substantially more important (w/r/t IV) than pyrophytes and intermediates, but as burn severity increased, pyrophytes became more important than mesophytes. This nding contrasts assertions that wild res in the eastern US may accelerate mesophication (Reilly et al 2022) and is aligned with patterns observed in western US forests, where higher-severity re shifts ecosystems toward more re-resilient communities (Nemens et al 2022;Cocking et al 2014). The burn severity at which pyrophytes in our study became more important (CBI = ~ 2.0) is particularly noteworthy, because prescribed res in this area rarely exceed a CBI of 1.5 (Winkenbach 2020).…”
Section: Discussionsupporting
confidence: 43%
“…In this, at low burn severities mesophytic species were substantially more important (w/r/t IV) than pyrophytes and intermediates, but as burn severity increased, pyrophytes became more important than mesophytes. This nding contrasts assertions that wild res in the eastern US may accelerate mesophication (Reilly et al 2022) and is aligned with patterns observed in western US forests, where higher-severity re shifts ecosystems toward more re-resilient communities (Nemens et al 2022;Cocking et al 2014). The burn severity at which pyrophytes in our study became more important (CBI = ~ 2.0) is particularly noteworthy, because prescribed res in this area rarely exceed a CBI of 1.5 (Winkenbach 2020).…”
Section: Discussionsupporting
confidence: 43%
“…A 2015 post-fire vegetation change study found that low and moderate-severity fire had little impact on the vegetative composition of the basin, with high-severity fire being primarily responsible for shifts away from conifer cover and towards shrub and meadow cover (Naranjo 2015). This is congruent with best available science on vegetative succession post-fire, which suggests that high-severity fire is often required to create fire-driven forest conversion in California ecosystems (Coop et al 2020, Nemens et al 2022. Attempts to use prescribed fire, which burns at low-to-moderate-severity, to combat conifer encroachment in meadows have found that this kind of fire removes lodgepole pines that are smaller in diameter than 20 cm but that there is little effect on larger trees (Frenzel 2012).…”
Section: Wildfire As Vehicle For Vegetative Succession/meadow Restora...supporting
confidence: 77%
“…Many studies have found that multiple consecutive fires are necessary to achieve conversion from forest to non-forest vegetation in the SN (White and Long 2019, Nemens et al 2022, Paudel et al 2022. The fires in question in the 3+ burn areas all occurred between 1973-1997, and from 1976-1998 meadow extent in those areas actually increased by 130.88%, the most marked increase seen in any of the meadow change analyses (See figure 8).…”
Section: Evidence For Managed Wildfire Increasing Meadow Areamentioning
confidence: 99%